Does Employee Resilience Exacerbate the Effects of Abusive Supervision? A Study of Frontline Employees' Self-Esteem, Turnover Intention, and Innovative Behaviors. Issue 5 (4th July 2021) - Bani-Melhem, Shaker; Quratulain, Samina; Al-Hawari, Mohammad Ahmad
ABSTRACT: Drawing on self-enhancement theory, this study examines the exacerbating influence of employee resilience on the relationship between abusive supervision and employee reactions, namely employee self-esteem, turnover intention and innovative behaviors. Two waves of survey data were collected from 205 frontline employees of hospitality organizations in the UAE, and structural equation modeling was used to analyze the model. The findings suggest that the negative relationship between abusive supervision and employee self-esteem is stronger when employees have high resilience. The mediating effect of self-esteem on the relationship between abusive supervision and turnover intention or innovative behaviors is also significant for highly resilient employees. These findings provide novel insights by highlighting the previously unexplored exacerbating role played by employee resilience in the abusive supervision-employee work outcomes relationship in the hospitality context.